Measuring tourism and environmental sciences students' attitudes towards sustainable tourism. (November 2020) - Arrobas, Fernando; Ferreira, Jéssica; Brito-Henriques, Eduardo; Fernandes, António
Highlights: Tourism and environmental sciences' students are compared. Tourism students highlight topics related to "Profit" and "People". Sustainability literacy in tourism cannot solely depend on the interest of teachers. Tourism academic programmes should be adapted to teach "strong sustainability". Environmental sciences professors could be invited to lecture in tourism courses.